Q: Solve 4r plus 6 equals 14?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-2=4r+s s=-4r-2 or s=-(4r+2)

It is 4r + 12s

Since 4R and R both contain a like term (R), you can combine them: 5R would be 4R plus R simplified

4r +3 = 3r-2 r + 3=-2 r=-5 basically collect terms so that you get one coefficient of r (in this case 4r on one side and 3r on the other. To get the three r over to the other side you subtract 3r on both sides.) Then r+ 3=-2, so that's simple algebraic manipulation.

4r + 4 = 5r 4r - r = 3r 4r x r = 4r^2 4r/r = 4

Related questions

4r + 13 = 57subtract 13 from both sides:4r + 13 - 13 = 57 -134r = 44divide both sides by 4 to solve for r:4r/4 = 44/4r = 11

-4r+6=14 isn't an inequality, its a linear equation. Anyway... -4r+6=14 (-6) -4r=8 (/4) -r=2 (x-1) r=-2

s = -2 -4r

-2=4r+s s=-4r-2 or s=-(4r+2)

If you mean: 10+4r = 30 then it works out that r = 5

r=8

7r = 3r - 527r (- 3r) = 3r - 52 (- 3r)4r = - 524r / 4 = -52 / 4r = -13

so 26 = 4r so r = 6½

It is 4r + 12s

2r + 2s = 50 2r - s = 17 therefore 4r - 2s = 34 Add so that you can eliminate one of the variables: 2r + 2s = 50 4r - 2s = 34 ---------------- 6r + 0s = 84 Solve for r: 6r = 84 r = 14 Substitute r into one of the original equations: 2(14) + 2s = 50 28 + 2s = 50 2s = 22 s = 11 Doublecheck with the other original equation: 2(14) - 11 = 28 - 11 = 17

Since 4R and R both contain a like term (R), you can combine them: 5R would be 4R plus R simplified

4r +3 = 3r-2 r + 3=-2 r=-5 basically collect terms so that you get one coefficient of r (in this case 4r on one side and 3r on the other. To get the three r over to the other side you subtract 3r on both sides.) Then r+ 3=-2, so that's simple algebraic manipulation.